Competitive Advantage as A Link Between the Influence of Intellectual Capital and CSR on Financial Performance - Komang Tri Yasrawan; Desak Nyoman Sri Werastuti; Edy Sujana (Jurnal Ilmiah Akuntansi, 2023)
This study aimed to empirically prove the influence of intellectual capital and corporate social responsibility on competitive advantage and its implications for the financial performance of MSMEs in the Buleleng Regency. The population in this study were MSMEs throughout Buleleng Regency, which amounted to 57,216 MSMEs. Determination of the number of samples using the technique of Isaac & Michael with a significance level of 5% obtained 346 MSMEs. The sample was selected using the purposive sampling technique. Data analysis was used SEM-PLS with the help of SmartPLS Version 3. The results showed that intellectual capital and CSR positively and significantly affected MSMEs' competitive advantage. Intellectual capital and CSR had a positive and insignificant effect on MSMEs' financial performance. The competitive advantage positively and significantly affected MSMEs' financial performance. Competitive advantage perfectly mediates the influence of intellectual capital and CSR on MSME financial performance.